Pelaksanaan Pembelajan Bernyayi Unisono di Kelas VII SMP Negeri 9 Solok Selatan - Husen As Sidiq; Olan Yogha Pratama (EDUMUSIKA, 2025)
This research aims to provide a comprehensive overview and practice of the application of unison singing learning in the seventh grade of SMP Negeri 9 Solok Selatan. This research is qualitative with a descriptive approach. The main tool used for this research is the researcher themselves, supported by writing instruments and a mobile phone. Data collection was conducted through observation, interviews, literature studies, and documentation. The data analysis process includes data collection, data identification, data classification, data clarification, and conclusion formulation. The research findings demonstrate that the implementation of unison singing learning in the seventh grade of SMP Negeri 09 Solok Selatan is carried out optimally, although teachers face difficulties in formulating learning indicators and limitations in learning media that result in the learning process not being fully optimal. The teacher only utilises the whiteboard and textbooks as learning media, allowing students to express their creativity. In the learning process, the use of learning media is very limited, confined to the whiteboard and cultural arts books. The teacher applies a discovery learning approach that enables students to actively seek and find information on their own. From the researcher’s observations, many students do not fully understand the concept of singing in unison and applying the correct vocal techniques, resulting in their inability to sing with the right tempo and pitch, caused by the teacher's lack of understanding of unison singing material which leads to difficulties for students in learning unison songs.